Analysis of the Psychological Development of Students During the Covid-19 Pandemic at MI MQ AN – NUUR - Mida Midiawati; Bunga Septria Vionita; Endah Robiatul Adawiyah (Indonesian Journal of Educational Science and Technology, 2022)
Psychology is a science that studies psychological activity or symptoms that are reflected in human behavior. The existence of psychology provides insight to determine the behavior of each individual, therefore psychology is very much needed for educational staff. This study aims to analyze the psychological development of students during the Covid-19 pandemic at MI MQ AN-NUUR from a psychological perspective. In addition to analyzing what kind of learning does not make students feel bored and bored during the Covid-19 period and what impact will occur if students' anxiety continues due to assignments at each meeting. The type of research used is descriptive qualitative. Collecting data in this study using interview techniques, and observation. The data analysis technique used in this study was to collect samples of data recording in the form of student behavior.